Menelisik Kekerasan Politik Berbasis Gender dalam Pilkada Kota Tangerang Selatan Tahun 2020 dan Dampak terhadap Keterwakilan Perempuan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze gender-based political violence in the 2020 Regional Head Elections in South Tangerang City and its impact on women’s representation in politics. The case analyzed involves social media attacks against Rahayu Saraswati Djojohadikusumo during her campaign for Deputy Mayor, in which an old photo of her while pregnant was used as material for sexually charged attacks. This study employs a qualitative method using a case study approach through literature review. The analysis utilizes Kate Manne’s theory of misogyny, which views misogyny as a social mechanism within the patriarchal system to control and discipline women entering the public sphere. The results of the study indicate that gender-based political violence manifests in the form of the moral delegitimization of women, digital intimidation or harassment, policing of women in public spaces, and the objectification of women’s bodies. These phenomena demonstrate that gender bias remains a barrier for women in securing equal space in local political contests.